Educational policies for e-learning teaching in universities after the pandemic - Tippe Marmolejo, Sindy Diamela (2021)
Introduction: In this article, based on the theoretical exploration, the need to propose proposals towards the construction of an educational policy of the minimum necessary for the e-learning modality in the university has been identified in the context of the Covid-19 pandemic. Background: Consequently, the heuristic and hermeneutical method were proposed, from which it follows that the virtualization of Peruvian education has meant an accelerated and unplanned process, from which the methodology applied in online teaching has evidenced great similarities with respect to face-to-face education. Discussion: It is necessary to establish new basic conditions for the quality of the e-learning educational service at the higher university level, which allow university institutions to adapt both to the demands of the new educational market and to the profiles of their potential students. Likewise, for its part, each government in turn must develop the pertinent steps to generate optimal conditions that help reduce access gaps and that related to digital skills.